The Effect of Realistic Mathematics Education Approach and Learning Motivation To Improving Higher Order Thinking Skills By Controlling Students Intelligence Quotient - Suyono, Suyono; Minarti, Minarti; Wiraningsih, Eti Dwi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aimed to determine whether students' HOTS could be improved by using the Realistic Mathematics Education (RME) approach. More specifically, this research wants to know the effect of the RME approach on HOTS, it will be studied from students' learning motivation and will be controlled for students' Intelligence Quotient (IQ). The research design used was pretest-posttest control group design with covariables and the implementation of the research design was factorial design by level (2 X 3). The research samples were 110 twelfth grade students from two schools in East Jakarta in the 2022/2023 academic year. The results of the study showed that the increase in HOTS of students who were taught using the RME approach was higher than students who were taught with conventional learning after controlling for students' IQ. There are differences in HOTS abilities between students with high, medium, and low motivation after controlling for student IQ. There is an influence between the learning approach and learning motivation on HOTS abilities after controlling for students' Intelligence Quotient.